The prediction of carbon monoxide exhaust emission diesel engine using artificial neural network / Mohd Kamarul Ariffin Abd Hadi and Sulaiman Muhammad Suffian - Abd Hadi, Mohd Kamarul Ariffin; Muhammad Suffian, Sulaiman (2004)
This project in title the prediction of carbon monoxide exhaust emission diesel engine using artificial neural network concerns with measurement and analysis of carbon monoxide. When talking about the prediction of carbon monoxide exhaust emission diesel engine using artificial neural network it is including with understanding of thermodynamics concepts and analysis about diesel engine that always been discuss especially when create the graph using the neural network. The results has been proof by experiments and observations due to the profile that present..